Formula optimization for garlic and pepper-flavoured puffed snacks - Brian H. Wilkinson; Wiwat Wangcharoen; Tipvanna Ngarmsak (Songklanakarin Journal of Science and Technology (SJST), 2006)
Herbs show high potential as functional ingredients in Thai snacks. Garlic was the most preferred herb in snacks, followed by holy basil, and pepper. This study was to determine the amount of spices such as garlic and pepper to be added to the products to beneficially improve the health status of the consumer without detrimental effect on the flavour and taste. The Box-Behnken (k = 3, nc = 3) response surface design was used to create a model to determine the optimum garlic and pepper flavour for puffed snacks. Specified quantities of salt (1-2 %(w/w)), garlic (0-4 %(w/w)), and pepper (0-4 %(w/w)) were used in the design. Fifteen spiced snacks were evaluated by 30 Thai panelists. The model showed the optimum pepper quantity of 0.7 % (w/w) and salt and garlic of no more than 1.10 and 2.80 %(w/w), respectively. If 25 g of the puffed snacks were eaten daily the consumer would get enough garlic to satisfy its daily requirements, but not enough pepper to get its purported health benefits. However, as the Thais use copious quantities of pepper in most other dishes, it is likely that eating 25 g of the proposed functional snack with their other dishes would more than likely provide enough pepper to give them the health benefits from this herb.